2013
DOI: 10.1111/1440-1681.12109
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptors in augmented vasoconstrictor responses to endothelin‐1 in chronic intermittent hypoxia

Abstract: Chronic intermittent hypoxia (CIH) contributes to the development of cardiovascular diseases in patients with obstructive sleep apnoea. Many studies have shown an association between increased circulating endothelin (ET)-1 levels and CIH. The aim of the present study was to determine the role of ET receptors in altered aortic function in an animal model of CIH. Rats were subjected to CIH (Fi o2 9% for 1 min, repeated every 2 min for 8 h/day, 7 days/week) for 3 weeks. After 3 weeks, the rats were killed and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 38 publications
3
20
1
Order By: Relevance
“…This result was different from our previous research that BQ788 could significantly reduce ET‐1‐mediated contractile responses in aortas and pulmonary arteries (Guo et al. ; Wang et al. ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This result was different from our previous research that BQ788 could significantly reduce ET‐1‐mediated contractile responses in aortas and pulmonary arteries (Guo et al. ; Wang et al. ).…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, these results were consistent with previous studies of ET‐1‐mediated artery and pulmonary dysfunction after CIH exposure (Guo et al. ; Wang et al. ), but few studies has reported ET‐1 and ET receptors changes in coronary arteries after CIH.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…During endothelial dysfunction, there is increased responsiveness to ET-1 along with increased expression of ET A receptors, which mediate a potent vasoconstrictor response in addition to decreased endothelial ET B receptor expression associated with functional decline of endothelium-dependent vasodilation [49,50]. Hyperhomocysteinemia has been demonstrated to induce endothelial dysfunction by activating ET A receptors and thereby shifting the balance towards enhanced contractility [51].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic intermittent hypoxia (CIH) is regularly used in animals to reproduce the recurring drops in arterial oxygen saturation that characterize respiratory patterns of sleep apnoea (SA) patients . CIH induces an elevation of arterial blood pressure that depends on exaggerated activity of peripheral chemoreceptors, leading to high activity of the sympathetic nerves and vascular dysfunction . In the central nervous system, CIH leads to increased levels of oxidative stress and neuronal apoptosis likely underlying cognitive impairments, and support for such findings can also be inferred by recent studies in humans showing reduced cortical thickness in both adult and pediatric SA patients.…”
Section: Introductionmentioning
confidence: 99%